KNOWLEDGE AND AWARENESS OF USE OF OZONE THERAPY IN DENTISTRY - G, Pushpaanjali.; Ganesh S, Balaji; Rani, Leslie (International Journal of Psychosocial Rehabilitation, 2020)
Ozone is a triatomic oxygen molecule that is formed when ultraviolet rays or a discharge of electricity causes oxygen atoms to combine in groups of three temporarily. It has been found to kill bacteria fungi viruses and parasites. The aim of this study is to create awareness and knowledge of use of ozone therapy in dentistry among dental students. The Questionnaires have been prepared and distributed to 100 participants of undergraduate and postgraduate dental students. The resulting data have been analyzed using statistical software. Descriptive statistical analysis was carried out and chi square test was used, and p value was calculated. Most of the participants of the survey were aware about the use of ozone therapy in dentistry. 68% of people accept that ozonated nanobubbles water has a bactericidal effect. 73% of people accept that gaseous ozone has more effective microbicidal properties than aqueous ozone. Within the limitations of study, a level of moderate awareness was present among the dental students. In future usage of ozone therapy can be incorporated in dental practices.